2014
DOI: 10.1016/j.jtcvs.2013.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Micropapillary and solid subtypes of invasive lung adenocarcinoma: Clinical predictors of histopathology and outcome

Abstract: Micropapillary and solid subtypes are common in tumors greater than stage I, with size ≥2.5 cm, pure solid type, and maximal standardized uptake value of ≥7, which were predictors for poor DFS. The presence of the micropapillary subtype was a single prognostic factor for OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
151
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(169 citation statements)
references
References 17 publications
(16 reference statements)
18
151
0
Order By: Relevance
“…Lepidic predominant subtype is known to result in better prognosis compared to other histologic subtypes (2). In contrast, micropapillary and solid predominant subtypes are known to result in poorer prognosis (7)(8)(9)(10). However, the reason for these differences remains unclear (4,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lepidic predominant subtype is known to result in better prognosis compared to other histologic subtypes (2). In contrast, micropapillary and solid predominant subtypes are known to result in poorer prognosis (7)(8)(9)(10). However, the reason for these differences remains unclear (4,11).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the invasive adenocarcinoma subtypes were significantly associated with recurrence and survival (3,4,6). Micropapillary and solid predominant subtypes are known to be poorer prognostic (7)(8)(9)(10); however, the reason for this remains unclear (4,11). The most valuable prognostic factor in non-small cell lung cancer is the pathological stage (6).…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, this group consists of tumor cells that grow in papillary tufts lacking fibrovascular cores, in contrast to true papillary structures which contain fibrovascular cores. Numerous studies have highlighted the poor prognosis of this histologic pattern in lung carcinoma (13,14,22,(31)(32)(33)(34)(35)(36). As stated previously, studies have shown that solid and micropapillary predominant tumors have the worst prognosis among the histologic subtypes.…”
Section: Issues With Current Histologic Classification Systemmentioning
confidence: 78%
“…Additional evidence suggests that the micropapillary pattern may in and of itself be a robust predictor of both prognosis and survival (14,20) and associated with poor outcomes (21,37). Furthermore, it has recently been suggested that the presence or absence of the micropapillary pattern may be an important prognostic indicator and impact survival (32)(33)(34). Rather than use the 5% increment as suggested by the IASLC classification, studies demonstrated that a micropapillary pattern of >1% of the tumor, resulted in metastasis and worse prognosis when compared to patients with no evidence of this histologic subtype (31).…”
Section: Issues With Current Histologic Classification Systemmentioning
confidence: 99%
“…Several studies have demonstrated that resected lung adenocarcinomas with micropapillary-predominant pattern show increased recurrence and mortality rates (2,3,(12)(13)(14). Moreover, even very small fractions of micropapillary pattern (1%, 5%, and 10%) have been associated with poor patient outcomes in multiple series (15)(16)(17). It has been hypothesized that these small fractions of micropapillary pattern may represent the micropapillary subtype of STAS (7).…”
mentioning
confidence: 99%